First distributional record of an Indo-Pacific porcupine puffer fish Diodon holocanthus (Diodontidae) from the Gopalpur coast, Bay of Bengal. (27th January 2015) - Mahapatro, Debasish; Naik, Subrat; Behera, Durga Prasad; Mishra, Rajani Kanta; Panda, Sudarshan
Abstract : The occurrence of the Indo-Pacific porcupine puffer fish Diodon holocanthus (Linnaeus, 1758) was recorded on 17 November 2013 on the Gopalpur coast of the Ganjam district, Odisha, as the first distributional record of this species from the east coast of India. Recordings appeared to increase after the event of the super cyclone 'Phailin', which occurred during 12 October 2013. Since then, many incidents of bycatch were observed from the Gopalpur coast. This poisonous porcupine puffer posed a subsequent threat to local anglers by damaging their fishing nets and by reducing the catch of commercially important fishes. However, a lack of substantial information regarding this puffer from the Gopalpur coast makes it difficult to correlate the facts.